2003
DOI: 10.1086/375837
|View full text |Cite
|
Sign up to set email alerts
|

From the Heart of the Ghoul: C and N Abundances in the Corona of Algol B

Abstract: Chandra Low Energy Transmission Grating Spectrograph observations of Algol have been used to determine the abundances of C and N in the secondary star for the first time. In order to minimize errors arising from an uncertain coronal differential emission measure as a function of temperature, the analysis was performed relative to similar observations of an adopted '' standard '' star, HR 1099. It is demonstrated that HR 1099 and Algol are coronal twins in many respects and that their X-ray spectra are very sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 59 publications
4
35
1
Order By: Relevance
“…Circumstantial evidence against such an explanation can be found in the abundance analysis of the active RS CVn-type binary HR 1099, for which independent analyses of Chandra and XMM-Newton observations obtained at different times yielded very similar values for quiescent coronal abundances (Brinkman et al 2001;Drake et al 2001). Moreover, Drake (2003b) has found similar abundances in the coronae of HR 1099 and its ''coronal twin,'' the active late-type component of the Algol binary.…”
Section: Coronal Abundancesmentioning
confidence: 98%
See 3 more Smart Citations
“…Circumstantial evidence against such an explanation can be found in the abundance analysis of the active RS CVn-type binary HR 1099, for which independent analyses of Chandra and XMM-Newton observations obtained at different times yielded very similar values for quiescent coronal abundances (Brinkman et al 2001;Drake et al 2001). Moreover, Drake (2003b) has found similar abundances in the coronae of HR 1099 and its ''coronal twin,'' the active late-type component of the Algol binary.…”
Section: Coronal Abundancesmentioning
confidence: 98%
“…For a value of ¼ 2:4, it has been found that this function represents the Chandra transmission grating instrumental profile to within photon counting statistics for lines with a few thousand counts or less (Drake 2003c). Spectra line fitting was undertaken using the FITLINES utility in the PINTofALE spectral analysis package (Kashyap & Drake 2000).…”
Section: Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Here we focus on the determination of the differential emission measure distribution and elemental abundances; for a comparison of the coronal spectra of HR1099 and Algol B we refer to Drake (2003).…”
Section: A Worked Out Example: Algolmentioning
confidence: 99%